Rola biskupów Rzymu w sporach doktrynalnych starożytnego Kościoła - Wygralak, Paweł (Vox Patrum, 2018)
This article presents the role of the bishops of Rome in the resolution of three doctrinal disputes (nestorianism, monophysitism, monothelitism) that hit the community of the Church between the 5th and the 7th centuries. Both the teaching of Nestorius and Eutyches were unequivocally condemned by the contemporary bishops of Rome, respectively Celestine and Leon the Great. Their teachings were confirmed by the general councils of Ephesus (431) and Chalcedon (451). Solving the problem of monothelitism has caused even more difficulties to the Holy See because of the attitude of Honorius I, who supported the erroneous teaching of the Patriarch of Constantinople, Sergei. Thus, the work discusses the actions of the subsequent bishops of Rome (especially John IV, Theodore, Martin I and Agathon) for restoring orthodoxy, which resulted in the adoption of resolutions condemning monothelitism by the Third Council of Constantinople (680-681). The article was primarily written on the basis of the preserved correspondence between heresiarchs and the bishops of Rome, the bishops of Rome and the emperors, as well as the resolutions of synods and councils.